The role of local wisdom values in Rateeb Meuseukat dance learning at elementary school teacher education, faculty of teacher training and education, Syiah Kuala University - Fitri, Aida; Basri, Novysa; Saputra, Rudy Juli; Halim, Fauziatul (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
The problem found was that students did not understand the role of local wisdom values in the Rateeb Meuseukat Dance. In fact, in the implementation of the knowledge transfer process in Rateeb Meuseukat dance learning carried out by lecturers to students, the local wisdom values contained in the Rateeb Meuseukat dance are very important to convey to students who will later use them in everyday life with the community to develop character. who loves his own culture in the  elementary school teacher education department of Syiah Kuala University. The aim of this research is to foster the role of local wisdom values in Rateeb Meuseukat dance learning and Islamic character education in students through instilling dance values. Data collection uses observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and data verification. The results of this research were that students in the  elementary school teacher education department of Syiah Kuala University, through the role of local wisdom values in learning the Rateeb Meuseukat Dance, directly found that students in the  elementary school teacher education department of Syiah Kuala University were able to dance the Rateb Meuseukat Dance and the role of the wisdom values of the Rateeb Meuseukat Dance, namely Aqidah values. worship, moral values) and muamalah values can be incorporated into the dance learning process so as to foster Islamic character education in students which will be carried into everyday life with society. The conclusion from the research results is that the role of local wisdom values through learning the Rateeb meuseukat dance increases students' understanding and knowledge of Aqidah values (worship values, moral values) and muamalah values thereby fostering character education in everyday life with the community.